Hubungan Budaya dan Pendidikan Islam dalam Pengembangan Budaya Melayu di Kecamatan Tanjung Pura Kabupaten Langkat - Diah Nurita; Muhammad Saleh; Ahmad Fuadi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to determine the relationship between culture and Islamic education in the development of Malay culture in Tanjung Pura District, Langkat Regency. And the research was carried out in August 2022. The approach used is a quantitative approach. The technique used in sampling namelyStratified Random Sampling. The instrument used in this study was in the form of a non-test, namely a questionnaire or questionnaire. While the correlation technique used isproduct moment. The results showed that the results of the correlation test withproduct moment shows that the value of r count is 0.71. Based on the data interpretation table for the r value, the number 0.71 is between 0.70 and 0.90. So it can be concluded that there is a strong or significant relationship between culture and Islamic education. accept or in other words there is a correlation between Culture and Islamic education. whether there is a significant relationship between the two variables. To prove this, the authors conducted a study on the title which was conducted by 151 people. Due to the large population, the researchers determined the sample based on the opinion that